Web-CMS based as teaching materials to improve students’ digital literacy - Bina Rahayu Setyasih; S. Supriyatin; Hanum Isfaeni (Research and Development in Education (RaDEn), 2024)
Technology advances and the profusion of information resources has the need to be accompanied by the students’ digital literacy and critical thinking skills. Website is the example of technological advances that are still rarely used as Content Management System (CMS) in learning. The purpose of this research is to develop website-based teaching materials to increase students’ digital literacy on material about cell. Research and development (R&D) conducted used ADDIE model. The development produces website-based teaching materials (Power Web Cell) which are later tested for the feasibility and the effectiveness in improving digital literacy of grade XI student on cell material. The product effectiveness test was caried out on 30 grade XI students who were selected using simple random sampling technique. The data was retrieved from digital literacy questionnaires measuring five areas. Hypothesis testing was conducted using paired sample t-test on pretest and posttest results. The results show that the developed Power Web Cell is feasible based on its feasibility tests’ result and is effective in improving students’ digital literacy. The content presented addresses more current issues and provides more interactive features, is recommended on developing website.